The prevalence and distribution of the flexor carpi radialis brevis muscle in the Turkish population - Akkoc, R. F.; Aksu, F.; Emre, E.; Ogeturk, M. (Nature Portfolio, 2022)
The flexor carpi radialis brevis (FCRB) is a very rare anomalous muscle that is usually asymptomatic but may cause various pathologies, such as radial-sided wrist pain. The aim of this study was to determine the prevalence of FCRB in the Turkish population, its location, and sex differences. Forearm, wrist, and hand magnetic resonance images of 849 individuals aged 18-65 years were retrospectively evaluated in this study. The survey found an FCRB prevalence of 4%, with a prevalence of 3.6% among women and of 4.7% among men. However, the difference between the sexes was not statistically significant (p = 0.629). The origin of all 34 FCRBs identified was the distal third of the anterior aspect of the radius; the insertion site of 28 was the second metacarpal bone, whereas that of the remaining 6 was the os trapezium. In conclusion, the data of this study report the prevalence of FCRB for the first time in the Turkish population, which will contribute to radiological and surgical evaluations in the region and help in early and accurate diagnosis of various pathological conditions that may be caused by FCRB.
Keywords: Wrist